A new, complex hyaline larger benthic foraminifer, Bigaella orbitoidiformis n. gen. n. sp., from the upper Bartonian-Priabonian of NW Turkey. (July 2022) - Özcan, Ercan; Mitchell, Simon F.; Pignatti, Johannes; Simmons, Michael D.; Yücel, Ali Osman; Robinson, Natalie
Abstract: The upper Bartonian–Priabonian shallow-marine deposits in the Biga Peninsula (NW Turkey) contain some hyaline larger benthic foraminifers (LBF) with a test architecture similar to 'orbitoidiform' foraminifers, but displaying some distinctive and complex morphological features that are recorded here for the first time. These coarsely porous specimens are characterized by a flat, disc-shaped, fragile, and smooth test with a layer of equatorial chambers/chamberlets, surrounded by poorly developed lateral chamberlets, never forming a discrete layer on either side of the equatorial layer. The nepionic stage is very distinctive because the bilocular embryonic apparatus is followed by a semi-rounded, notably large auxiliary chamber with a characteristic wavy outline, and consecutive cyclical chambers. The cyclical chamber arrangement is later transformed into annular cycles with numerous, complex arcuate- to cup-shaped chamberlets, as observed in equatorial sections. Bigaella orbitoidiformis Özcan, Mitchell, Pignatti, Simmons, and Yücel, n. gen. n. sp., is established for these specimens, and placed within the family Eoannulariidae Ferràndez-Cañadell and Serra-Kiel, emended herein. The new genus occurs together with Caudriella Haman and Huddleston and Epiannularia Caudri (both originally established from the American bioprovince) and the genus Linderina Schlumberger (found both in the Tethys and the American bioprovinces), together with other typical Western Tethyan LBFs. A comparison of the new genus with the aforementioned taxa is given. UUID: http://zoobank.org/ab917e30-86d3-4bc2-8115-d17cf75f5d79 .